Pemberdayaan Badan Usaha Milik Desa (BUMDes) Desa Talang Pauh Bengkulu Tengah - Benardin Benardin; Bambang Agoes Hermanto; Hutapia Hutapia (UNIB Press, 2024)
In order to develop the Talang Pauh Jaya Village Business Entity (BUMDes) business unit. This service activity is carried out by providing additional knowledge about the Feasibility Study of business development for BUMdes managers in Talang Pauh Jaya village. Considering the importance of the business feasibility analysis required by BUMDes, it is necessary to provide training and assistance in analyzing business feasibility development planning so that BUMDes managers can develop their businesses professionally and profitably. The Village Business Management Agency (BUMdes) of Talang Pauh Village, Pondok Kelapa District, Central Bengkulu Regency can generally understand and understand several important aspects related to business feasibility analysis and business unit development planning. This community service program or activity can be continued and improved because of the high enthusiasm of BUMdes managers and residents of Talang Pauh Village, Pondok Kelapa subdistrict, Central Bengkulu Regency.